Effectiveness of an Electronic Alert for Hypotension and Low Bispectral Index on 90-day Postoperative Mortality: A Prospective, Randomized Trial. (December 2016) - McCormick, Patrick J.; Levin, Matthew A.; Lin, Hung-Mo; Sessler, Daniel I.; Reich, David L.
Abstract : Background: We tested the hypothesis that an electronic alert for a "double low" of mean arterial pressure less than 75 mmHg and a bispectral index less than 45 reduces the primary outcome of 90-day mortality. Methods: Adults having noncardiac surgery were randomized to receive either intraoperative alerts for double-low events or no alerts. Anesthesiologists were not blinded and not required to alter care based upon the alerts. The primary outcome was all-cause 90-day mortality. Results: Patients (20, 239) were randomized over 33 months, and 19, 092 were analyzed. After adjusting for age, comorbidities, and perioperative factors, patients with more than 60 min of cumulative double-low time were twice as likely to die (hazard ratio, 1.99; 95% CI, 1.2 to 3.2; P = 0.005). The median number of double-low minutes (quartiles) was only slightly lower in the alert arm: 10 (2 to 30) versus 12 (2 to 34) min. Ninety-day mortality was 135 (1.4%) in the alert arm and 123 (1.3%) in the control arm. The difference in percent mortality was 0.18% (99% CI, −0.25 to 0.61). Conclusions: Ninety-day mortality was not significantly lower in patients cared for by anesthesiologists who received automated alerts to double-low states. Prolonged cumulative double-low conditions were strongly associated with mortality. Abstract : In a randomized trial of over 19, 000 patients, the duration of double low was slightly reduced when alarms occurred during this condition, but 90-day mortality was not affected.